Analisis Disiplin Kerja, Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Pegawai Badan Riset dan Inovasi Medan - Putri Five Br Galingging; Siswa Pratama (Lembaga Pengembangan Kinerja Dosen, 2025)
The potential of the workforce is an important element that determines the success of an organization, especially in facing the challenges posed by globalization. Although a company has facilities and other resources that are very helpful, without competent human resources, the operational activities of the agency will not operate properly. Thus, human resource management is a crucial factor that needs to be considered. The expected achievement of this study is to examine the influence of work discipline, leadership, and work environment on employee work habits at the Medan City Research and Innovation Agency. This study is associative, which means it aims to understand the relationship between variables. This study indicates that employee performance is positively and significantly influenced by the work environment (regression coefficient 0.768; tcount 3.829 > ttable 2.0369), leadership (regression coefficient 0.419; tcount 4.459 > ​​ttable 2.0369), and work discipline (regression coefficient 0.354; tcount 3.458 > ttable 2.0369). With a significance of 0.000 < 0.05 and high Fcount, the model is declared significant at 46.147 higher than Ftable 2.72, then the three factors collectively affect performance significantly. Therefore, employee performance at the Medan City Research and Innovation Agency is positively and significantly influenced by work discipline, leadership, and work environment together.